2021
DOI: 10.1007/s12034-021-02547-7
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature oxidation of CO using alkali- and alkaline-earth metal-modified ceria-supported metal catalysts: a review

Abstract: The present review devoted to the complete oxidation of CO using alkali-and alkaline-earth metal (AM/AEM)-modified ceria supported/mixed with noble metal and non-noble metal (NM). The AM/AEM-modified Ce supported/mixed with noble metal showed comparable CO oxidation with unmodified catalyst. However, AM/AEMmodified NM showed higher CO oxidation at lower temperature compared to the unmodified catalyst. The AM and AEM modifications were responsible for the formation of oxygen vacancies in Ce, which leads to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…It is well established that catalysts require a minimum temperature to get activated, and once they attain this equivalent activation energy, they accelerate reaction kinetics toward completion of the desired reaction. Hence, it can be realized that a catalyst not only has to possess great conversion activity but also needs to show significantly great activity at lower temperatures as could be observed in LTC systems …”
Section: Catalytic Postcombustion Pollutant Mitigation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that catalysts require a minimum temperature to get activated, and once they attain this equivalent activation energy, they accelerate reaction kinetics toward completion of the desired reaction. Hence, it can be realized that a catalyst not only has to possess great conversion activity but also needs to show significantly great activity at lower temperatures as could be observed in LTC systems …”
Section: Catalytic Postcombustion Pollutant Mitigation Strategiesmentioning
confidence: 99%
“…Hence, it can be realized that a catalyst not only has to possess great conversion activity but also needs to show significantly great activity at lower temperatures as could be observed in LTC systems. 194 Gu et al 195 fabricated a novel Al 2 O 3 -LaAlO 3 -ZrO 2 -TiO 2 mixed oxide which exhibited exceptional low temperature catalytic activity with 90% CO, 75% NO, and total HC conversion at 196, 200, and 200 °C respectively. Use of mesoporous base catalyst materials such as γ-Al 2 O 3 exhibits exceptional properties such as a well-developed pore structure, substantial number of hydroxyl groups, and high specific surface area, which are among the suitably expected properties for a catalyst support.…”
Section: B100mentioning
confidence: 99%
“…Similarly, Aneggi et al [81] have indicated the surface-dependency of soot oxidation with the nanoshaped materials, i.e., ceria nanocubes exposing (100) crystal planes and nanorods with (100), (110) and partly (111) crystal facets, affecting the soot oxidation activity in a positive manner as compared to polycrystalline ceria dominated by (111) planes. the nanoshaped materials, i.e., ceria nanocubes exposing [100] crystal planes and nanorods with [100], [110] and partly [111] crystal facets, affecting the soot oxidation activity in a positive manner as compared to polycrystalline ceria dominated by [111] planes. In addition, ceria-based nanostructured catalysts doped with La and Nd were hydrothermally synthesized and investigated in soot combustion [87].…”
Section: Soot Oxidationmentioning
confidence: 99%
“…The latter triggers unique opportunities for the rational design of highly active metal oxides by following a general optimization approach involving the modulation of various interrelated factors, such as the size and morphology of parent oxides [29,96,98,99]. In addition, surface promotion (mainly by an alkali or alkaline earth metal) can be employed as an additional tool to fine-tune the local surface chemistry of mixed oxides [29,100,101].…”
Section: Co Oxidationmentioning
confidence: 99%
See 1 more Smart Citation